2018
DOI: 10.1002/mc.22868
|View full text |Cite
|
Sign up to set email alerts
|

MALAT1 promotes the colorectal cancer malignancy by increasing DCP1A expression and miR203 downregulation

Abstract: The long non-coding RNA MALAT1 has been proved to promote the cell proliferation, drug resistance, invasion, and metastasis of colorectal cancer (CRC) in vitro and in vivo by regulating the expression of various oncogenes and their protein products. Our previous work discovered that the expression of the mRNA-decapping enzymes 1a (DCP1A) is upregulated in CRCs. However, the relationships between MALAT1 and DCP1A in the development of CRC and the underlying mechanisms are still unclear. In this study, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 39 publications
3
31
0
Order By: Relevance
“…Among others, MALAT1 increases tumor formation in many cancers, including gastric, gallbladder, and lung cancer in vivo [77][78][79][80]. Importantly, MALAT1 has been shown in several studies to promote colorectal cancer cell development via proliferation, migration, and invasion [81,82], and is considered a potential therapeutic target for colon cancer. MALAT-1 was significantly inhibited by all delivery methods and free drugs ( Figure 11B) compared to positive control cells.…”
Section: Inhibition Of Malat-1 Expression In Hct116 Cancer Cellsmentioning
confidence: 99%
“…Among others, MALAT1 increases tumor formation in many cancers, including gastric, gallbladder, and lung cancer in vivo [77][78][79][80]. Importantly, MALAT1 has been shown in several studies to promote colorectal cancer cell development via proliferation, migration, and invasion [81,82], and is considered a potential therapeutic target for colon cancer. MALAT-1 was significantly inhibited by all delivery methods and free drugs ( Figure 11B) compared to positive control cells.…”
Section: Inhibition Of Malat-1 Expression In Hct116 Cancer Cellsmentioning
confidence: 99%
“…By enhancing Serine/arginine-rich splicing factor kinase (SRPK)1-induced SRSF1 phosphorylation, MALAT-1 promoted CRC cell proliferation, invasion, and migration via upregulation of Protein kinase (PRK)A kinase anchor protein (AKAR)9; 79 and by acting as decoy for miR-203, MALAT-1 induced the expression of mRNAdecapping enzyme (DCP)1A, resulting in increased CRC cell proliferation, invasion, and chemoresistance. 80 Activation of the MALAT-1/miR-145/Sex determining region Y-box (Sox)9 signaling axis promotes proliferation, invasion, and migration and inhibits cell cycle progression and apoptosis in CRC. 81 CRC progression is also influenced by MALAT-1/miR-129-5p/high-mobility group box (HMGB)1 signaling.…”
Section: Lung Carcinomamentioning
confidence: 99%
“…17 Wu et al have shown that MALAT1-miR203-DCP1A axis is associated with the malignancy of CC. 39 Sun et al have demonstrated that MALAT1 enhances the proliferation and inhibits the apoptosis of OC cells via sponging miR-503-5p. 40 Herein, miR-101-3p was predicted to be a target gene of MALAT1 by StarBase, and this target relationship was validated by dual-luciferase reporter assay and RNA pull-down assay in CC cells.…”
Section: Dovepressmentioning
confidence: 99%